Pressure-dependent NOS activation contributes to endothelial hyperpermeability in a model of acute heart failure. Issue 6 (23rd November 2018) - Chignalia, Andreia Z.; Isbatan, Ayman; Patel, Milan; Ripper, Richard; Sharlin, Jordan; Shosfy, Joelle; Borlaug, Barry A.; Dull, Randal O.
Abstract : Aims: Acute increases in left ventricular end diastolic pressure (LVEDP) can induce pulmonary edema (PE). The mechanism(s) for this rapid onset edema may involve more than just increased fluid filtration. Lung endothelial cell permeability is regulated by pressure-dependent activation of nitric oxide synthase (NOS). Herein, we demonstrate that pressure-dependent NOS activation contributes to vascular failure and PE in a model of acute heart failure (AHF) caused by hypertension. Methods and results: Male Sprague–Dawley rats were anesthetized and mechanically ventilated. Acute hypertension was induced by norepinephrine (NE) infusion and resulted in an increase in LVEDP and pulmonary artery pressure (Ppa ) that were associated with a rapid fall in Pa O2, and increases in lung wet/dry ratio and injury scores. Heart failure (HF) lungs showed increased nitrotyrosine content and ROS levels. L-NAME pretreatment mitigated the development of PE and reduced lung ROS concentrations to sham levels. Apocynin (Apo) pretreatment inhibited PE. Addition of tetrahydrobiopterin (BH4) to AHF rats lung lysates and pretreatment of AHF rats with folic acid (FA) prevented ROS production indicating endothelial NOS (eNOS) uncoupling. Conclusion: Pressure-dependent NOS activation leads to acute endothelial hyperpermeability and rapid PE by an increase in NO and ROS in a model of AHF. Acute increases in pulmonary vascular pressure, without NOS activation, was insufficient to cause significant PE. These results suggest a clinically relevant role of endothelial mechanotransduction in the pathogenesis of AHF and further highlights the concept of active barrier failure in AHF. Therapies targetting the prevention or reversal of endothelial hyperpermeability may be a novel therapeutic strategy in AHF.